The effects of fermentation of Qu on the digestibility and structure of waxy maize starch - Wu, Wenhao; Zhang, Xudong; Qu, Jianzhou; Xu, Renyuan; Liu, Na; Zhu, Chuanhao; Li, Huanhuan; Liu, Xingxun; Zhong, Yuyue; Guo, Dongwei (Frontiers in Plant Science, 2022)
The fermentation of Qu (FQ) could efficiently produce enzymatic modified starch at a low cost. However, it is poorly understood that how FQ influences the waxy maize starch structure and the digestion behavior. In this study, waxy maize starch (WMS) was fermented by Qu with different time, and starches were isolated at each time-point, and its physico-chemical properties and structural parameters were determined. Results showed that the resistant starch (RS)，amylose content , the average particle size (D [4,3]) the ratio of peaks at 1022/995 cm-1 and the onset temperature of gelatinization (To) increased significantly after 36 h. Conversely, the crystallinity, the value of peak viscosity (PV), breakdown (BD), gelatinization enthalpy (ΔH) and the phase transition temperature range (ΔT) declined significantly after 36h. It is noteworthy that smaller starch granules appeared at 36 h, with wrinkles on the surface, and the particle size distribution also changed from one sharp peak to bimodal. We suggested that the formation of smaller rearranged starch granules was the main reason for the pronounced increase of RS during FQ process.